Communication experiences of women surviving postpartum depression in Indonesia - Wahyu Utamidewi; Yanti Tayo; Pamungkas Satya Putra; Mohamad Febrianto; Achmad Naufal Hafidz (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
The presence of a baby in the family becomes a happy event, but it turns out that the feeling of happiness is not immediately felt by the mother who gave birth. Improper information regarding postnatal mental health makes childbirth a sad thing for a mother. This study aims to construct experiences, feelings, and meanings regarding Postpartum Depression. So that by knowing the experiences, feelings, and meanings about Postpartum Depression, information about the condition of women after giving birth can be better. This study uses a qualitative research method with a phenomenological approach. This study was conducted on 8 women who experienced Postpartum Depression after giving birth to their first child or second child. Data was collected by means of unstructured interviews with open-ended questions. This research is useful for seekers of information about Postpartum Depression where they will know how to avoid being exposed to Postpartum Depression.